Genre-Based Approach in Teaching BIPA - Basori Basori; Elva Riezky Maharany (Universitas Negeri Padang, 2021)
Knowledge of various teaching strategies is one of the important things that teachers need to have. In this case, every teacher must equip themselves with a variety of teaching strategies to achieve success in teaching BIPA. The text-based approach is one of the approaches that teachers can apply in teaching BIPA. There have been many studies that prove the success of this approach. However, the use of text-based approaches to teaching BIPA is still rare. Therefore, this article aims to provide a brief overview of the use of a text-based approach in teaching BIPA. This paper will present an understanding of a text-based approach in general, the advantages of using a text-based approach in teaching BIPA, and examples of using a text-based approach in teaching BIPA.